2018
DOI: 10.4236/jtst.2018.42003
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Special Finishes on the Functional Properties of Cotton Fabrics

Abstract: This study demonstrated that the changes in functional properties of both woven and knit cotton fabrics were determined to evaluate the performance of different special finishes. Here, 100% cotton fabrics were treated with different types of finishing chemicals at different formulations. To assess the performance of different finishes on fabric properties, GSM, bursting strength, tensile strength, dimensional stability, absorbency, crease recovery angle with ASTM and AATCC methods were done. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…On the other hand, micro silicone emulsion provides sufficient wet rubbing, soft handle, acceptable shade change, increased colour yield and good absorbency to both colored fabrics. Chowdhury (2018) [26], the study demonstrated that the changes in functional properties of both woven and knit cotton fabrics were determined to evaluate the performance of different special finishes. He used100% cotton fabrics treated with different types of finishing chemicals at various formulations.…”
Section: ‫ف‬ ‫براير‬ 2022mentioning
confidence: 99%
“…On the other hand, micro silicone emulsion provides sufficient wet rubbing, soft handle, acceptable shade change, increased colour yield and good absorbency to both colored fabrics. Chowdhury (2018) [26], the study demonstrated that the changes in functional properties of both woven and knit cotton fabrics were determined to evaluate the performance of different special finishes. He used100% cotton fabrics treated with different types of finishing chemicals at various formulations.…”
Section: ‫ف‬ ‫براير‬ 2022mentioning
confidence: 99%
“…Application of a polymeric composition on the surface of a textile material with inclusion of substances having diverse functional purposes (antibacterial, fire retardant, water repelling, etc.) in composition of substances is a universal way to provide the textile materials with required special properties [4,5]. To this end, wide use of styrene-acrylic polymers forming the base of compositions due to high optical, physical and mechanical properties is known [6,7].…”
Section: перспективним способом захисту забарвлень від дії світла є зmentioning
confidence: 99%